Konsep al-‘Adl dalam Harta Gono Gini Perspektif Masyarakat Sampang Madura - Harisah .; Kutsiyatur Rahmah (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
Textually in the Qur’an and the Hadith there is no explanation regarding the distribution of property gono-gini. The distribution of assets is born from the habits of the people, which they think is right and fair. So that every place of distribution is not always the same. Similarly, the Madurese community. Based on this, there are two problems that become the study in this study, namely: the distribution of gono-gini assets in Madura and justice in gono-gini assets according to the Madurese people by using qualitative methods with the type of field research. This data was obtained by interview, observation and documentation. This research proves that the distribution of gono-gini assets in the Madurese community is carried out by: first, division involving two families. Second, it involves religious leaders. Third, by involving the village head. Fourth, involving the court. Whereas justice according to the Madura community does not have to be the same. However, if the assets are sufficient to meet their needs, then that is considered fair.